Melt Memory Effect on Biaxially Oriented Random Copolyamides: Direct Evidence for Stretch-Induced Crystal Retention above the Equilibrium Melting Point - Yunqi Xu (349428) (2025)
In the processing of semicrystalline polymers, the oriented crystal through flow-induced crystallization (FIC) represents a significant phenomenon that can profoundly influence the final properties of materials. This study investigates the melting and crystallization behavior of biaxial stretch-induced crystal structures in BOPA56/512 (biaxially oriented PA56/512 films) with varying copolymerized compositions at temperatures above Tm, utilizing DSC, XRD, FTIR, and in situ POM. Results reveal that BOPA56/512 with relatively high PA512 mol % in the random copolymer PA56/512 develops distinct and long-range shish-kebab structures. These structures exhibit remarkable stability, persisting even above the equilibrium melting point (Tm0). Notably, the thermal history effect from biaxial stretching, which elevates the crystallization temperature, persists even upon heating to the molten state. Additionally, increasing the heat treatment temperature induces a γ-α form transition in BOPA56/512. Conversely, with decreasing PA512 mol % content, BOPA56/512 forms only irregular and shorter secondary crystals, and the increasing temperature induces merely changes in the d-spacing of the γ form rather than a phase transition. CP/MAS NMR and crystallization Gibbs free energy (Gc) calculations suggest that shish-kebab formation and γ-α transition in high PA512 mol % BOPA56/512 result from better chain mobility and lower Gc of PA512. Remarkably, even when heated to 90 °C above Tm, these shish kebab/secondary crystal structures are partially preserved. Upon cooling of the molten state, these preserved structures serve as initial nucleation sites for recrystallization. This unprecedented observation of stable shish-kebab structures persisting at temperatures significantly above (Tm0) may represent a novel finding in the field. Results demonstrate that in PA56/512 random copolymers, the biaxially stretch-induced oriented structures do not dissolve completely into relaxed random coils under the influence of a single temperature. Instead, they undergo partial relaxation into crystalline precursors, maintaining some degree of structural order even at elevated temperatures. The results of this study provide a theoretical basis for designing and regulating the aggregation structure and macroscopic properties of biaxially oriented random copolyamide films.